THE INFLUENCE OF ADDING NUTRIENT ELEMENTS IN POC COMPOSITION ON ROOT AND LEAF GROWTH IN PAKCOY (Brassica rapa L.) PLANTS USING HYDROPONIC CULTIVATION SYSTEM - Ady Dwi Tegar, Ahmad Nurul Hakim An Nasif; Sugiarto, Ady Dwi Tegar; Rahman, Nanik Astuti (jurnal ATMOSPHERE, 2023)
Planting with a hydroponic system is a technique for cultivating plants without using soil media, but instead using water as a medium for cultivating plants. So that planting with a hydroponic system can use narrow land. So a study was conducted with the aim of applying Liquid Organic Fertilizer (POC) with the Indonesian National Standard (SNI) in a hydroponic planting system by adding POC constituent nutrients to the growth of roots and leaves of mustard greens, by adding a dose POC concentration of 0%, 9%, 12%, and 15% by analyzing samples of 0, 7, 14, 21, 28, 35 days to obtain better growth of pakcoy vegetables. The best growth of pakcoy plant roots was obtained from a concentration of 15%, obtained a length of 18.75 cm. The best growth in leaf width of the oajcoy plant was obtained from a concentration of 0% or without POC, the leaf width was 5.75 cm.